Breathprints of childhood obesity: changes in volatile organic compounds in obese children compared with lean controls. Issue 1 (27th March 2014) - Alkhouri, N.; Eng, K.; Cikach, F.; Patel, N.; Yan, C.; Brindle, A.; Rome, E.; Hanouneh, I.; Grove, D.; Lopez, R.; Hazen, S. L; Dweik, Raed A.
Summary Objective The objective of this study was to investigate changes in volatile organic compounds (VOCs) in exhaled breath in overweight/obese children compared with their lean counterparts. Study design Single exhaled breath was collected and analyzed per protocol using selective ion flow tube mass spectrometry (SIFT‐MS). Results Sixty overweight/obese children and 55 lean controls were included. Compared with the lean group, the obese group was significantly older (14.1 ± 2.8 vs. 12.1 ± 3.0 years), taller (164.8 ± 10.9 vs. 153.3 ± 17.1 cm) and more likely to be Caucasian (60% vs. 35.2%); P < 0.05 for all. A comparison of the SIFT‐MS results of the obese group with the lean group revealed differences in concentration of more than 50 compounds. A panel of four VOCs can identify the presence of overweight/obesity with excellent accuracy. Further analysis revealed that breath isoprene, 1‐decene, 1‐octene, ammonia and hydrogen sulfide were significantly higher in the obese group compared with the lean group (P value < 0.01 for all). Conclusion Obese children have a unique pattern of exhaled VOCs. Changes in VOCs observed in this study may help to gain insight into pathophysiological processes and pathways leading to the development of childhood obesity.